Women Writers Constructing Foremothers - Grundy, Isobel (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2024)
How far were women writers of the long eighteenth century aware of literary foremothers, of a women’s tradition? Did they seek to build such a tradition and to claim its legacy? This paper begins and ends with two highly personal experiences of relating to literary grandmothers. In between, it looks at homage paid to Restoration writers seen as originators, like Katherine Philips, Aphra Behn, Mary Astell, and others, at allusion and influence, at perceptions of relationship and declarations of alliance sometimes spanning several generations, at both the gradual consolidating and the eroding of knowledge about previous ages, and at attempts by Elizabeth Elstob, Mary Scott, and Elizabeth Ogilvy Benger to order and disseminate this knowledge and to foster the idea of a female literary inheritance.